1964
DOI: 10.3181/00379727-117-29529
|View full text |Cite
|
Sign up to set email alerts
|

Role of Calcium in Complement Dependent Hemolysis.

Abstract: CALCIUM IN COMPLEMENT DEPENDENT HEMOLYSIS 179 and ocular defects. Multiple malformations were rare. The teratogenic dose of Congo red did not produce any alteration in maternal serum protein components during the expected period of teratogenic activity. This is contrasted to the situation found following treatment with trypan blue.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

1965
1965
1985
1985

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 2 publications
0
9
0
Order By: Relevance
“…In addition, PNHE, lacking a C'-activating mechanism (antibody coat), are deprived of the ability to exert any direct influence on the initiation and localization of C' action (4,20). The need for participation of fluid phase early C' components in PNHE lysis in acid serum is attested to by the dependence of acid hemolysis on Mg++ (2), implying that at least C'2 is involved in fluid phase events. Taken in the framework of our current knowledge of the role of C'2 in C'-dependent lysis, it seems reasonable to conclude that these C'2-mediated fluid phase events are preceded by action of C'1 (21) (and possibly C'4) and that they are concerned with rendering C'3a capable of attachment (possibly by activation) to PNHE (4,22,23).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, PNHE, lacking a C'-activating mechanism (antibody coat), are deprived of the ability to exert any direct influence on the initiation and localization of C' action (4,20). The need for participation of fluid phase early C' components in PNHE lysis in acid serum is attested to by the dependence of acid hemolysis on Mg++ (2), implying that at least C'2 is involved in fluid phase events. Taken in the framework of our current knowledge of the role of C'2 in C'-dependent lysis, it seems reasonable to conclude that these C'2-mediated fluid phase events are preceded by action of C'1 (21) (and possibly C'4) and that they are concerned with rendering C'3a capable of attachment (possibly by activation) to PNHE (4,22,23).…”
Section: Discussionmentioning
confidence: 99%
“…The experiments utilizing decayed PNHE clearly demonstrate that cell bound C'2 plays no direct role during the attachment of C'3a. Although PNHE presumably go through a state equivalent to PNHEC'3a in vivo, such cells are probably destroyed by C'3b and C'3c almost immediately, since PNHE studied in vitro are resistant to hemolysis in the absence of Mg++ (2).…”
Section: Discussionmentioning
confidence: 99%
“…However, the latter observations were made in a dilute C' reagent. Subsequent studies in this laboratory have shown that the need for Ca++ in immune lysis is not absolute; EA will undergo maximal lysis in undiluted human serum or in serum diluted 1: 2 even in the presence of Na2-MgEDTA (28). Apparently sufficient C'la can be generated under such circumstances to initiate and sustain the sequence of events leading to C'-dependent hemolysis.…”
mentioning
confidence: 99%
“…pH reduction might result in en- Recognition that classical immune hemolysis produced by human C' has a pH optimum similar to that of the PNH hemolytic system supports the argument that the C' system plays the predominant role in in vitro PNH red cell lysis. Immune hemolysis and poly I-induced hemolysis of normal red cells have recently been shown to proceed in the absence of Ca++, provided that Mg++ is supplied and whole human serum is used as the C' source (3,21); PNH hemolysis also displays an absolute requirement for Mg++ but not for Ca++ (6). Thus the PNH hemolytic system resembles other human C'-dependent hemolytic systems not only in its pH optimum, but also in divalent cation requirements.…”
Section: Of Various Eac' Intermediates In Immunementioning
confidence: 94%